KEBUTUHAN DAN HAMBATAN MAHASISWA DALAM MENJALANI PEMBELAJARAN BLENDED LEARNING DI UNIVERSITAS AUFA ROYHAN - Olivia Feby Harahap (Universitas Aufa Royhan Di Kota Padangsidipuan, 2022)
ABSTRACT Blended learning model or combination of online and offline learning modelsbetween lecturers and students.Blended learningnew in learningat Aufa Royhan University in Padangsidimpuan,the reason behindwhy choose this learning modelbecause none otherdue to the spread of the Covid-19 virus.Blended learning systemapplied by students cause some problemsincluding poor internet connection, expensive internet quotaand material that is difficult to understand,so thatlead to ineffective learningand efficient to implement.The purpose of this research to explore needsand student barriersin undergoing blended learning.This research uses qualitative research methodswith a phenomenological study research design. Data retrievalby conducting in-depth interviews(in depth interview) and documentation. The results of this study got 3 themes, namely:Theme 1:Difficult to attend when offlinedifficult to access online, Theme 2: Students need internet facilitiesduring blended learning, Theme 3: Variety of overflowsblended learning feeling.Conclusion from research resultsshows thatstudent needs and barriersin undergoing blended learning categorized intounpleasant experiencedue to many obstaclesexperienced by students when doing blended learning.Researchers suggestto all students to be able to followand able to take advantage oftechnological sophisticationespecially in learning. Keywords : learning barriers, Experience, Blended learning, Student